The Influence of Religious Education on Radical Religious Understanding Among Students of the State Islamic Institute: English - Purwanto; Wibowo, Furqon Edi; Jandra , Mifedwil; Rosman, Arieff Salleh; Abu-Hussin, Mohd Fauzi (UIN Raden Mas Said Surakarta, 2022)
The aim of this research was to investigate the level of religious understanding radicalism among students of the Public Faculty and Religious Faculty, respectively. The initial hypothesis was that the level of religious understanding radicalism of the students in the Public Faculty would be higher than that of the students in the Religious Faculty. The research employed an ex post facto method and used t-test to analyze the data. The study was conducted in 2018 at the State Islamic Institute of Surakarta, an Islamic religious college in Surakarta. The research population consisted of all students from 22 departments in the academic year of 2016, totaling 10,980 people. Samples were drawn from each department, with a quota of 10 students per department, resulting in a total of 220 sample members. The data collection used a questionnaire of religious understanding radicalism, which was tested for validity and reliability. Data analysis included a sample randomness test, data normality test, and variant homogeneity test. The results showed that although the level of religious understanding radicalism was higher among students in the Public Faculty than those in the Religious Faculty, the hypothesis was not statistically proven. The study suggests that religious education cannot be solely correlated with formal education background and that students' interactions with extra campus organizations, both on and off-campus, play a significant role in shaping their religious understanding radicalism. Additionally, the religious education process in the Public Faculty at the State Islamic Institute of Surakarta could make students more moderate in their religious understanding.